1993
DOI: 10.1016/0014-5793(93)80739-h
|View full text |Cite
|
Sign up to set email alerts
|

Purification of hydroxylamine oxidase from Thiosphaera pantotropha

Abstract: Thiosphaerupuntorropha, a Gram-negative heterotrophic nitrifying bacterium, expresses a soluble 20 kDa monomeric periplasmic hydroxylamine oxidase that differs markedly from the hydroxylamine oxidase found in autotrophic bacteria. This enzyme can use the periplasmic redox proteins, cytochrome cssl and pseudoazurin as electron acceptors, both of which can also donate electrons to denitrification enzymes. A model of electron transfer is proposed, that suggests a coupling of nitrification to denitrification and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(29 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…It has been reported that the biochemical mechanism of ammonia oxidation in several heterotrophic nitrifying bacteria, Arthrobacter globiformis and Paracoccus pantotropha , is similar to the above-mentioned process of the AOBs. However, NH 2 OH oxidation is catalyzed by a nonheme Fe protein in both bacteria1314.…”
mentioning
confidence: 99%
“…It has been reported that the biochemical mechanism of ammonia oxidation in several heterotrophic nitrifying bacteria, Arthrobacter globiformis and Paracoccus pantotropha , is similar to the above-mentioned process of the AOBs. However, NH 2 OH oxidation is catalyzed by a nonheme Fe protein in both bacteria1314.…”
mentioning
confidence: 99%
“…The role of nitrification in lithotrophs is clearly the provision of energy for growth, however, the purpose of nitrification in heterotrophs is somewhat more obscure. Nitrification consumes reductant and is postulated to be required in heterotrophs for the maintenance of redox poise [2,3] In addition to the key role played by all nitrifiers in the global nitrogen economy, these organisms are also able to degrade hydrocarbon pollutants through the activity of ammonia monooxygenase (Amo). This enzyme possesses a relaxed substrate specificity allowing turnover of alkanes, alkenes, chlorinated and brominated short-chain aliphatics and aromatic compounds [4,5].…”
Section: N H I + C H + Wqhz] Nhxoh+hxo+ Wql 2 Nhxoh+hzomentioning
confidence: 99%
“…To raise antibodies to HAO, the protein was purified according to Wehrfritz et al (1993) and conjugated to bovine serum albumin. Antibodies were raised in sheep by Immunogen International.…”
Section: Methodsmentioning
confidence: 99%
“…europaea also expresses another, distinct, cytochrome P460 with H A 0 activity, analogous to that of Methylococcus capsulatus (Bergmann & Hooper, 1994a;Zahn et al, 1994). In contrast, the H A 0 from Pa. denitrificans is a monomeric protein of approximately 18.5 kDa containing non-haem iron (Wehrfritz et al, 1993 ;Moir et al, 1996a). The hao gene of N .…”
Section: Chemolithoautotrophic Nitrifying Bacteria Such Asmentioning
confidence: 99%
See 1 more Smart Citation